IMPOLITENESS UTTERANCES EXPRESSED BY GORDON RAMSAY IN "HELL'S KITCHEN" REALITY SHOW - Azhari, Chud Radeffy; Ambalegin, Ambalegin; Arianto, Tomi (IdeBahasa, 2024)
This study investigated several Impoliteness utterances expressed by Gordon Ramsay in "Hell's Kitchen" reality show. This study used descriptive qualitative analysis to categorize the data. Observational methods and taking a note were applied to collect the data by Sudaryanto. Following that, the data were analyzed using the competence - in equalizing technique and the Pragmatic Identity Method to examine the data in context. Impoliteness contained five strategies. There were 33 impoliteness strategies in the data. sixteen data of bald on record Impoliteness. nine data of negative impoliteness. four data of Positive Impoliteness. two data of sarcasm impoliteness. And two data of withhold impoliteness. Gordon Ramsay’s utterances in “Hell’s Kitchen” reality show mostly uttered bald on record impoliteness strategy. It was clear that the Gordon Ramsay as the speaker gave impoliteness comments by attacking the participants with unpleasant statements in the most direct